CULTURAL WORDS TRANSLATION STRATEGIES IN MARY HIGGINS CLARK'S NOVEL THE ANASTASIA SYNDROME AND OTHER STORIES - Fitriyah Fitriyah (Universitas Islam Sumatera Utara (UISU), 2021)
The translation of cultural words needs some consideration and recognition of the cultural achievements referred to in the Source Language (SL) text, and respect for all foreign countries and their cultures. Therefore, translating cultural words is quite difficult, because their structures cannot always be translated literally and, even tend to form new meanings. The aims of this research are to describe the cultural words and analyze the translation strategies used in Mary Higgins Clark’s novel The Anastasia Syndrome and Other Stories, already translated into Indonesian entitled Sindrom Anastasia dan Kisah-kisah lainnya by Ade Dina Sigarlaki. This research is a qualitative descriptive study. The data are the cultural words in English (SL) and their translation in Indonesian (TL). Those are analyzed based on Newmark’s cultural categories and Baker’s translation strategies. The results show that there are 74 cultural words and four translation strategies in Mary Higgins Clark’s novel The Anastatia Syndrome and other stories: 1) Translation by a more general word (superordinate), 2) Translation by a more neutral/less expressive word, 3) Translation by cultural substitution, 4) Translation using a loan word or loan word plus explanation.